The Impact of Environmental, Social, and Governance Implementation on Financial Performance - Rahayu, Sari; Hastuti, Poppy Meilina Dian; Efendi, Mohamad Johan; Sutikno, Frendy (Jurnal Informatika Ekonomi Bisnis, 2025)
This study investigates the relationship between Environmental, Social, and Governance implementation and financial performance, with a particular focus on the mediating roles of corporate reputation and operational efficiency. Using a quantitative research design and Partial Least Squares Structural Equation Modeling, data from publicly listed companies across ESG-sensitive industries were analyzed to test the hypothesized relationships. The findings reveal that ESG implementation does not have a statistically significant direct effect on financial performance. However, it significantly influences corporate reputation and operational efficiency, both of which serve as strong mediators linking ESG initiatives to improved financial outcomes. These results support the integration of stakeholder theory, signaling theory, and the resource-based view in understanding the ESG-performance nexus. The study highlights the importance for firms to align ESG strategies with core operations and stakeholder expectations to unlock long-term financial value. Implications for corporate managers, investors, and policymakers are discussed, emphasizing ESG as a critical driver of sustainable competitive advantage.